YIELD RELATED MORPHOLOGICAL MEASURES OF SHORT DURATION COTTON GENOTYPES - M. J. Baloch; N. U. Khan; M. A. Rajput; W. A. Jatoi; S. Gul; I. H. Rind; N. F. Veesar (Journal of Animal and Plant Sciences, 2014)
The present studies were aimed to characterize the early maturing cotton genotypes and determine the relationship among earliness, yield and fiber quality traits. Eight upland cotton genotypes viz., CRIS-134, Sadori, Chandi, NIAB-78, AA-802, IR-3701, IR-1524 and FH-113 were included in the studies. The experiment was laid out in a randomized complete block design with four replications during 2012 at Sindh Agriculture University, Tandojam, Pakistan. The mean squares indicated significant (p≤0.01) differences among the genotypes for all the traits. The two cultivars i.e. CRIS-134 and Sadori were characterized as early maturing in terms of days to 1st flower, formed sympodial branches at relatively lower nodes, set 1st effective boll on lower sympodia, formed and opened maximum bolls at 90 and 120 days after planting (DAP) and weighed medium size bolls. For yield traits, maximum bolls plant-1, bigger bolls, higher seed cotton yield and more lint percentage were obtained from cultivars CRIS-134, Sadori, IR-3701 and FH-113. Regarding fiber traits, the longer staple with desirable micronaire were recorded by CRIS-134, AA-802 and FH-113. The correlation coefficient showed that sympodial branch length, bolls formed at 120 DAP, bolls plant-1 and seed index were significantly and positively correlated with seed cotton yield. The higher correlations of yield components with yield indicated their reliable use as indirect selection criteria to improve the seed cotton yield. Some important negative correlations of lint percentage with seed index, staple length and micronaire value were also recorded which indicated that a compromise level for lint percentage may be considered while improving staple length and fiber fineness in cotton.
Keywords: Short duration cotton; early maturity; seed cotton yield and fiber traits